Application of 18F-FDGPET/CT in primary isolated pulmonary solitary fibrous tumor - Shao, Mingyan; Fan, Sisi; Qi, Wanling (Frontiers in Medicine, 2025)
ObjectivePulmonary solitary fibrous tumors (SFTs) represent a rare clinical entity, with malignant variants demonstrating particularly aggressive behavior and metastatic potential. The diagnostic challenge in early-stage disease underscores the need for improved detection methods. This study evaluates the diagnostic utility of 18F-FDG PET/CT in distinguishing benign from malignant pulmonary SFTs and assesses its role in treatment response monitoring.MethodsWe performed a retrospective analysis of clinical characteristics and imaging findings in four histologically confirmed pulmonary SFT cases evaluated with 18F-FDG PET/CT at Jiangxi Provincial People’s Hospital (2020–2024).ResultsThe cohort exhibited heterogeneous clinical presentations: three patients reported chest tightness with pain, one had non-painful chest tightness, and two presented with concomitant cough. Notably, no cases demonstrated hemoptysis, productive sputum, or fever. Contrast-enhanced CT initially suggested malignancy in three cases and benign pathology in one. PET/CT revealed two cases with intense FDG avidity (preoperatively classified as malignant—one with peritoneal metastases) and two with minimal uptake (classified as benign). Histopathological confirmation of all surgical specimens established PET/CT’s 100% diagnostic accuracy for benign/malignant differentiation, compared to only 50% accuracy for contrast-enhanced CT.Conclusion18F-FDG PET/CT provides clinically valuable discrimination between benign and malignant pulmonary SFTs, while offering additional benefits in disease staging, biopsy guidance, treatment response assessment, and post-therapeutic surveillance.